Penerapan Pidana Tambahan Pembayaran Uang Pengganti Dalam Tindak Pidana Korupsi Guna Mewujudkan Keadilan - Herdiana, Fransisca; Chandra, Tofik Yanuar; Shodiq, M. D. (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
One way to return lost state money is to impose additional penalties in the form of replacement payments. This effort is to provide income to the state treasury from the results of replacement payments from corruption convicts. This study focuses on discussing the case of the Application of Additional Criminal Penalties in the Form of Replacement Payments in Corruption Crimes in accordance with the provisions regarding replacement penalties in Article 18 of Law Number 31 of 1999 concerning the Eradication of Corruption. The formulation of the problem raised in this study is how the procedure for implementing replacement payments in corruption crimes and how to apply additional replacement penalties in corruption crimes in order to realize justice. In this study, the author uses the theory of justice and the theory of criminal law. The research method used is a normative legal approach. This study uses a statute approach and a case approach which in principle originates from primary legal materials consisting of laws and judges' decisions, secondary legal materials consisting of books, research results, articles and tertiary legal materials from libraries, articles and websites. The legal material analysis technique uses grammatical interpretation techniques. The results of this study are that the Procedure for implementing replacement money in corruption cases is regulated in the Attorney General's Letter Number B-845/F/Fjp/05/2018, which regulates the stages of implementing court decisions, including the execution of additional criminal penalties in the form of an obligation to pay replacement money. Simultaneously with the issuance of the Court Decision Execution Order (P-48), the Head of the District Attorney's Office also issues an Asset Search Order (P-48A) to track the convict's assets. If the convict pays replacement money, the executing prosecutor provides a receipt (Form D-3) and hands over the money to the treasurer to be deposited into the state treasury within 1x24 hours. However, if within one month after the decision has permanent legal force the replacement money has not been paid, the prosecutor is obliged to confiscate the convict's property for execution. The application of additional criminal penalties for replacement money itself is regulated in Article 18 of Law No. 31 of 1999 in conjunction with Law No. 20 of 2001, which is generally accompanied by subsidiary penalties. In order to realize justice and optimize state financial recovery, it is better if the replacement money punishment is not accompanied by a subsidiary so that the perpetrators of corruption have no choice but to pay the replacement money. The suggestion in this study is to improve state financial recovery through replacement money, it is necessary to strengthen international cooperation in tracing assets from corruption hidden abroad in order to support the effectiveness of intelligence prosecutors in tracking assets. In addition, in the short term it is recommended that the Supreme Court issue a Circular Letter that makes the payment of replacement money a condition for obtaining remission and conditional release, so that perpetrators of corruption cannot avoid or choose to serve imprisonment as an alternative to paying replacement money